Evidence for rapid faunal change in the early Miocene of East Africa based on revised biostratigraphic and radiometric dating of Bukwa, Uganda. Issue 116 (March 2018) - Cote, Susanne; Kingston, John; Deino, Alan; Winkler, Alisa; Kityo, Robert; MacLatchy, Laura
Abstract: Field expeditions to Bukwa in the late 1960s and early 1970s established that the site had a small but diverse early Miocene fauna, including the catarrhine primate Limnopithecus legetet. Initial potassium-argon radiometric dating indicated that Bukwa was 22 Ma, making it the oldest of the East African early Miocene fossil localities known at the time. In contrast, the fauna collected from Bukwa was similar to other fossil localities in the region that were several million years younger. This discrepancy was never resolved, and due to the paucity of primate remains at the site, little subsequent research took place. We have collected new fossils at Bukwa, reanalyzed the existing fossil collections, and provided new radiometric dating. 40 Ar/ 39 Ar incremental heating ages on lavas bracketing the site indicate that the Bukwa fossils were deposited ∼19 Ma, roughly 3 Ma younger than the original radiometric age. Our radiometric dating results are corroborated by a thorough reanalysis of the faunal assemblage. Bukwa shares taxa with both stratigraphically older localities (Tinderet, Napak) and with stratigraphically younger localities (Kisingiri, Turkana Basin) perfectly corresponding to our revised radiometric age. This revised age for Bukwa is important because it indicates that significant faunal turnover may have occurred in East Africa between 20 and 19 Ma. Bukwa samples immigrant taxa such as large suids, large ruminants, and ochotonids that are absent from stratigraphically older but well-sampled localities in the region, such as Tinderet (∼20 Ma) and Napak (20 Ma). Further age refinements for Bukwa and the entire East African early Miocene sequence will help to constrain the timing of this faunal turnover event, of particular importance in paleoanthropology since this temporal sequence also provides us with what is currently our best window into the early evolution of cercopithecoid and hominoid primates.